2018
DOI: 10.1016/j.conbuildmat.2017.12.107
|View full text |Cite
|
Sign up to set email alerts
|

Mixture design and early age investigations of more sustainable UHPC

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 72 publications
5
42
0
1
Order By: Relevance
“…The second peak, observed by other authors [23], characterizes the contribution of slag to the hydration reaction; this contribution is not readily apparent given that the studied materials are mortars and the binder volume is small. The curves plotted however reveal that the peak heat flow becomes flatter as slag content rises [23,35]. Table 4 indicates both the measured and normalized characteristic values of the isothermal microcalorimetry curves; the substitution of cement by 30% and 60% slag results in a decrease of 18% and 51% of the primary peak heat flow, respectively.…”
Section: Hydration Reactionmentioning
confidence: 78%
See 2 more Smart Citations
“…The second peak, observed by other authors [23], characterizes the contribution of slag to the hydration reaction; this contribution is not readily apparent given that the studied materials are mortars and the binder volume is small. The curves plotted however reveal that the peak heat flow becomes flatter as slag content rises [23,35]. Table 4 indicates both the measured and normalized characteristic values of the isothermal microcalorimetry curves; the substitution of cement by 30% and 60% slag results in a decrease of 18% and 51% of the primary peak heat flow, respectively.…”
Section: Hydration Reactionmentioning
confidence: 78%
“…This phenomenon is directly correlated with the dilution effect of slag plus the fact that both hydraulic and pozzolanic reactions release less heat than Portland cement hydration [21,33,34]. The second peak, observed by other authors [23], characterizes the contribution of slag to the hydration reaction; this contribution is not readily apparent given that the studied materials are mortars and the binder volume is small. The curves plotted however reveal that the peak heat flow becomes flatter as slag content rises [23,35].…”
Section: Hydration Reactionmentioning
confidence: 81%
See 1 more Smart Citation
“…At present, there are two main methods to obtain the early‐strength PCEs: on the one hand, compounding inorganic or organic accelerators of cement slurry with ordinary PCE to make up complex early‐strength PCEs, these accelerators include calcium chloride, sodium sulfate, calcium sulfate, calcium nitrate, triethanolamine, diethanolamine, and so forth; however, the complex early‐strength PCEs have certain restrictions in practice such as higher dosage, corrosive to the steel, storage instability, and may decrease the later strength of concrete . On the other hand, according to the designability of PCE molecular structure, the research idea that preparing novel early‐strength PCE and exploring the influence of PCE molecular structure on the cement hydration process has been adopted as the main development direction of early‐strength PCE . According to Yamada et al ., the concrete that included the PCEs with longer polyoxyethlene (PEO) side chains had significantly shorter setting time.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of potassium in SMF could be higher than 15% due to the presence of potassium aluminosilicate (KAlSi 3 O 8 ) (Najamuddin et al 2019) or other impurities, such as potassium feldspar generally occurring in manganese oxide ore (Zhong et al 2017). Abdulkareem et al (2018) reported that high K 2 O content could contribute to the strength in the presence of silica and lime in the OPC-based binder. However, the role of K 2 O in AAB synthesis co-existed with MnO in SMF and their synergy with BFS, is not yet fully elucidated.…”
Section: Introductionmentioning
confidence: 99%